Factors affecting the implementation of immunization - Djauhar Ismail; Endy Paryanto; Tonny Sadjimin; Rachmat Soetrisno (Paediatrica Indonesiana, 1999)
Immunization coverage of vulnerable children is a critical indication ofsuccess in health development This study aimed to detennine the role of various factors in the basic immunization status of under five children. In Godean sulxiistrict, district of Sleman, Yogyakarta, interviews were conducted with 161 mothers of 14 to 59 months old children selected by stratified random sampling with the village as the unit of study and 27.3 per cent probability of being included in the study. Immunization status of children was recorded on an interval scale, with a value of 8 representing complete basic immunization status. We found that basic immunizationstatus of children had significant relation to the level of mother's knowledge concerning immunization, the educational background of both mother and father, family income, and the number of children (p < 0.05). From the factors, the level of mother's knowledge about immunization had the most relation to immunization status (relative contribution was 73.9 %). This factor was significantly influenced by the mother's formal educational background, the father's formal educational background, and family income (p < 0.05). Those factors necessarily should beincluded in the strategy of community education in order to increase theimmunization coverage.